الإيكو القلبي ودوره المبكر في تشخيص اختلاطات احتشاء العضلة القلبية - أحمد, هدى (Latakia University Journal -Medical Sciences Series, 2019)
شملت الدراسة 120 مريضاً قبلوا في وحدة العناية المشددة بتشخيص احتشاء عضلة قلبية حاد في الفترة الواقعة مابين 1/7/2005 – 1/9/2006، وقمنا بدراسة اختلاطات احتشاء العضلة القلبية المبكرة، والعلامات المنذرة باختلاطات متأخرة. - وقد تمت الدراسة بتخطيط صدى القلب 2D والدوبلر لكشف أم الدم، والخثرة البطينية وغيرها وكان وجودهما دلالة سيئة كذلك تم دراسة وظيفة البطين الأيسر، وحساب الجزء المقذوف الذي كان دليلاً سريرياً أكثر شيوعاً حيث لوحظ أن EF تنخفض لدى مرضى الاحتشاء القلبي المختلط بأم الدم أو خثرة. - كذلك زمن التباطؤ التاجي DT كان له أهمية في التنبؤ بحدوث الخثار بعد احتشاء العضلة القلبية. - وكان استعمال منسب درجة حركية الجدار له أهمية في التنبؤ بمضاعفات احتشاء العضلة القلبية الحاد حيث تدل العلامة (WMSI) مثلاً على ارتفاع كبير في نسب المضاعفات بعد الاحتشاء. - وقد كانت هناك منبآت تعتبر سلبية، ومنذرة على حصول اختلاط للاحتشاء (قصور قلب – خثار...) من أهمها: 1 – المشعر = INDEX . 0.6 2 – EF ≥ 40 %. 3 – احتشاء الجدار الأمامي. 4 – انخفاض DT زمن التباطؤ التاجي أقل من 140ملم ثا. 5 – سوء حركية الجدار. وهكذا فإن الإيكو القلبي، يمكن أن يكون وسيلة مهمة وسهلة الاستعمال لاستخدامه في الكشف المبكر عن اختلاطات احتشاء العضلة القلبية الحاد، ومعالجتها بالسرعة الممكنة والفعالة. The study involved 120 patients who were accepted in the intensive care unit for sever myocardial infraction between 1/7/2005 and 1/9/2006. We studied the complications of the early sever myocardial infraction, and the warning signs of late complications The study was carried by echocardiography 2D, and Doppler to check aneurysm, ventricular coagulum, and others whose presence was a bad. We studied the function of the left ventricule, calculated the size of herzstos which was a common clinical sign, and noticed that EF decreases in myocardial infraction patients which was accompanied by aneurysm or coagulum. The mitral lag time DT was important in predicting of coronary thrombosis following to myocardial infraction. The use of wall kenetic index in predicting with the complications of sever myocardial infraction, where (2) indicates a high increase in the rates of repercussions after infraction. There were some negative signs of repercussions of infractions (heart failure, thrombosis…) such as: 1- index >0.6 2- EF<40% 3- EF<40% 4- decrease of DT 5- mal kinetism of the wall. So the cardiac echo could be a significant tool easy to implement to use in early diagnosis of sever myocardial infraction complications as soon as possible.